A flux‐form conservative semi‐Lagrangian multitracer transport scheme (FF‐CSLAM) for icosahedral‐hexagonal grids. (23rd May 2014) - Dubey, Sarvesh; Mittal, Rashmi; Lauritzen, Peter H.
Abstract A high‐order incremental "remap‐type" transport scheme is presented (FF‐CSLAM). The scheme utilizes bi‐quadratic polynomial subgrid‐cell reconstruction functions based on the weighted least squares method. The integration of the reconstruction functions over flux areas, which is inherent in remap schemes, makes use of CSLAM approach of line integration. Though the formal order of the scheme is second order, yet quadratic subgrid scale polynomial reconstruction does lead to improvement in the overall accuracy of the scheme. Since the rigorous search for overlap areas between flux areas and grid cells is cumbersome, two simplifications have been suggested in the literature. The main objectives of this paper are (a) to formulate flux‐form CSLAM for the icosahedral‐hexagonal grid and (b) to assess the accuracy of two flux‐integral simplifications.